Kepengaturan tanpa Perlawanan Langsung: Program Pemetaan GPS Partisipatif di Taman Nasional Mae Tho, Thailand - Adrianus Venda Pratama Putra (BHUMI: Jurnal Agraria dan Pertanahan, 2020)
Agrarian conflict between the Karen people and the Royal Forestry Department (RFD) in the northern Thailand has been going on for a long time. The root of the problem is that Karen tenurial rights are not recognized, even they lived there for hundreds 0f years. Their access to the forest also restricted because the area is included in the Mae Tho National Park. The conflict eventually subsided after the acceptance of the GPS participatory mapping program initiated by NGOs and the government. The program was well-received without significant resistance. The proof is that 80% of residents in the village where this research takes place agrees with the program. Some residents even boast of the program, even the program prohibits local residents from expanding their land beyond the land they have occupied for hundreds of years. Departing from the Michael Foucault framework of governmentality and etnographic research method, there are seven reasons why the program could run effectively. First, land insecurity makes Karen people crave land recognition. Second, they accepted the idea of conservation due to the construction of marginality limits their choices. Third, migration reduces pressure on the land. Fourth, debt bondage. Fifth, the role of NGOs. Sixth, the use of local institutions and churches that campaign for program benefits. Seventh, the creation of a national park as a new economic space.Keywords: GPS participatory mapping; governmentality; conservation; debt; local institutions; NGOsIntisari: Konflik agraria antara orang Karen dan Royal Forestry Department (RFD) di pegunungan utara Thailand telah berlangsung lama. Pangkal masalahnya ialah orang Karen yang telah ratusan tahun tinggal di sana tidak direkognisi hak tenurialnya dan hendak dibatasi aksesnya ke hutan karena wilayah tersebut masuk ke dalam Taman Nasional Mae Tho. Konflik tersebut akhirnya mereda pasca diterimanya program pemetaan GPS partisipatif yang digagas oleh LSM dan pemerintah. Program tersebut diterima dengan efektif tanpa perlawanan berarti. Buktinya adalah  80% warga di lokasi riset setuju dengan program tersebut. Beberapa warga bahkan membanggakan program tersebut. Padahal program tersebut melarang warga sekitar meluaskan lahannya di tanah yang telah dihuni selama ratusan tahun. Berangkat dari kerangka pikir kepengaturan Michael Foucault dan metode riset etnografi, ada tujuh alasan mengapa program tersebut bisa berjalan efektif. Pertama, insekuritas atas tanah membuat orang Karen menginginkan rekognisi lahan. Kedua, konstruksi marjinalitas membatasi pilihan mereka sehingga ide konservasi harus diakomodasi. Ketiga, migrasi membuat tekanan atas tanah berkurang. Keempat, jerat hutang. Kelima, peran LSM. Keenam, penggunaan institusi lokal dan gereja yang mengkampanyekan manfaat program. Ketujuh, diciptakannya taman nasional sebagai ruang ekonomi baru.Kata Kunci: Pemetaan GPS partisipatif; kepengaturan; konservasi; utang; institusi lokal; LSM